Carbon Dots in a Matrix: Energy‐Transfer‐Enhanced Room‐Temperature Red Phosphorescence. (7th November 2019) - Wang, Bolun; Yu, Yue; Zhang, Hongyue; Xuan, Yuzhi; Chen, Guangrui; Ma, Wenyan; Li, Jiyang; Yu, Jihong
Abstract: High‐efficiency red room‐temperature phosphorescence (RTP) emissions have been achieved by embedding carbon dots (CDs) in crystalline Mn‐containing open‐framework matrices. The rationale of this strategy relies on two factors: 1) the carbon source, which affects the triplet energy levels of the resulting CDs and thus the spectral overlap and 2) the coordination geometry of the Mn atoms in the crystalline frameworks, which determines the crystal‐field splitting and thus the emission spectra. Embedding the carbon dots into a matrix with 6‐coordinate Mn centers resulted in a strong red RTP with a phosphorescence efficiency of up to 9.6 %, which is higher than that of most reported red RTP materials. The composite material has an ultrahigh optical stability in the presence of strong oxidants, various organic solvents, and strong ultraviolet radiation. A green‐yellow RTP composite was also prepared by using a matrix with 4‐coordinate Mn centers and different carbon precursors. Abstract : Die Punkte verbinden : Der Energietransfer (ET) von Kohlenstoffpunkten (CDs), die in kristalline Mn‐haltige offene Gerüstmatrizen eingebettet sind, führt zu hocheffizienter roter Raumtemperatur‐Phosphoreszenz. Durch die Variieren der CD‐Vorläufer und der Heteroatom‐Koordinationsgeometrien kann die Emissionen von rot zu grün/gelb verschoben werden.